Analysis of Warehouse Management System and 5S Method for Standardizing Raw Material Warehouse Layout in Rolling Door Production - Rani Setiawati; Tri Ngudi Wiyatno; Mega Purnamasari (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
PT Prestasi Cahaya Metalindo faces challenges in raw material warehouse management, including unstructured material storage, mixed material categories, incomplete labeling, and the absence of standardized location codes, which lead to inefficiencies in material retrieval and limited traceability between stock records and physical storage locations. This study aims to analyze the current warehouse condition and propose an improvement model using a conceptual Warehouse Management System (WMS) approach and the 5S method. The research applies a descriptive quantitative method with a case study approach, where data were collected through observation, interviews, documentation, material searching time measurement, 5S assessment, and stock data analysis. The WMS approach is applied as a conceptual and structured framework for warehouse identification and control, not as a digital software system, focusing on improving material coding, location identification, and stock-location integration based on physical warehouse conditions, while the 5S method is used to evaluate and improve workplace organization. The results indicate that the proposed improvement model provides a potential enhancement in warehouse performance under a designed condition scenario, where material searching time decreases from 10.5 minutes per item to 3.9 minutes per item and the 5S score increases from 43% to 84%, although these results represent a proposed system that has not yet been implemented in actual operational conditions and require further validation. This study highlights that integrating structured warehouse identification systems with workplace organization principles can improve warehouse efficiency in manufacturing environments.